2002
DOI: 10.1093/humrep/17.4.1112
|View full text |Cite
|
Sign up to set email alerts
|

A high hypospadias rate in The Netherlands

Abstract: We found a 4-fold higher than expected hypospadias rate, which may be explained by case ascertainment differences. The proportion of major cases was higher than generally assumed. This study provides evidence for substantial geographical differences. Explanations for temporal and geographical differences need to be explored. To monitor hypospadias rates and trends accurately, complete case ascertainment, including standardized classification of severity, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
3
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 29 publications
4
82
3
5
Order By: Relevance
“…An English study for the period 1992-1994 (Chambers and Malone 1999) based on a surgical series stated a policy to recommend surgery in virtually all cases of hypospadias. A Finnish study also reported a policy of surgical correction for minor cases (Aho et al 2000), and a small Dutch study for 2000 (Pierik et al 2002) found that 78% of cases had been recommended surgery, including one-quarter of glanular cases. Before the 1980s, a study in Rochester, New York (USA; Sweet et al 1974) on a single hospital series for the period 1940-1970 reported a surgical rate of 24%, with all surgical cases being either penile or with testicular-associated abnormalities, and an international registry study (Kallen et al 1986) reported surgery for 40% of cases in Hungary 1975, 31% in Sweden 1974, and 27% in Denmark in 1974-1976.…”
Section: Implementation Of Guideline To Exclude Glanular Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…An English study for the period 1992-1994 (Chambers and Malone 1999) based on a surgical series stated a policy to recommend surgery in virtually all cases of hypospadias. A Finnish study also reported a policy of surgical correction for minor cases (Aho et al 2000), and a small Dutch study for 2000 (Pierik et al 2002) found that 78% of cases had been recommended surgery, including one-quarter of glanular cases. Before the 1980s, a study in Rochester, New York (USA; Sweet et al 1974) on a single hospital series for the period 1940-1970 reported a surgical rate of 24%, with all surgical cases being either penile or with testicular-associated abnormalities, and an international registry study (Kallen et al 1986) reported surgery for 40% of cases in Hungary 1975, 31% in Sweden 1974, and 27% in Denmark in 1974-1976.…”
Section: Implementation Of Guideline To Exclude Glanular Casesmentioning
confidence: 99%
“…A previous international study of registries (Kallen et al 1986) found that in Sweden in 1974, 5% of cases were false positives, and in Hungary in 1975, 21% of cases were false positives. In a recent Dutch study, Pierik et al (2002) trained 30 child health center physicians in a standardized examination of newborns to detect hypospadias. Of the 60 boys referred to the pediatric urologist/endocrinologist as cases of hypospadias, seven had a preputial abnormality only.…”
Section: Implementation Of Guideline To Exclude Glanular Casesmentioning
confidence: 99%
“…For every marker, single-point and multipoint linkage analyses were obtained using the Allegro software. 33 Corresponding P-values were interpreted according to Lander and Kruglyak, 34 and P-values were estimated using the formula, P(LOD) ¼ 0.5 Â (w 2 1 42ln10 Â LOD). For the association analyses in the Swedish cohort, single marker and multiple-marker association tests were performed using Haploview.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of hypospadias ranges from 0.3 to 0.8% among male live births in Europe, Asia and North America. [1][2][3] In Sweden, the incidence of hypospadias is 0.3% since the beginning of the 1970s according to the annual Swedish Malformation Registry. 1,4 Hypospadias is considered to be a complex disorder caused by the interplay between environmental factors and effects of multiple genes.…”
Section: Introductionmentioning
confidence: 99%
“…Other international studies have suggested an increasing incidence of hypospadias. [1][2][3][4] The etiology is now beginning to be elucidated as mutations in both the MAMLD1 and the ATF3 genes have been identified to cause hypospadias. 5,6 However, most cases of hypospadias remain unexplained.…”
Section: Introductionmentioning
confidence: 99%